Topological pinning and flux flow in ceramic superconductors - López, D.; Decca, R.; de la Cruz, F. (Comisión Nacional de Energía Atómica; Argentina)
Fil: de la Cruz, F. Comisión Nacional de Energía Atómica; Argentina